Strategic Human Resource Management in the Era of Algorithmic Technologies: Key Insights and Future Research Agenda - Kim, Sunghoon; Khoreva, Violetta; Vaiman, Vlad (Human Resource Management, 2025)
ABSTRACTThis article presents a contemporary review of human resource management (HRM) research on algorithmic technologies, including artificial intelligence, machine learning, and natural language processing. By connecting these recent advancements to the long‐standing scholarly tradition of HRM‐technology relations, this review examines current knowledge on how algorithmic technologies are reshaping three key areas: (1) work structures and design, (2) HR delivery activities, and (3) the management of technology workers. Using a threefold conceptualization of technology—the tool view, proxy view, and ensemble view—this review explores how organizations employ algorithmic systems to enhance productivity, how the human agency interacts with and resists these technologies, and how broader social, cultural, and institutional contexts shape the use of algorithms in HRM. Additionally, this article offers suggestions for future research, highlighting the unique opportunities algorithmic technologies provide to HR scholars for making enduring contributions to the broader conversations on HRM and technology.